Transformation of Religious Education Curriculum to Improve Public Understanding of Cash Waqf Schemes in Indonesia - Misbahul Anwar (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The fundamental challenge in optimizing Islamic philanthropy in Indonesia lies in the low public understanding of cash waqf schemes, rooted in the dominance of traditional literacy. The narrow paradigm viewing waqf solely as immovable assets persists due to the religious education curriculum's dependence on classical jurisprudence doctrines, which lack discussion on contemporary financial instruments. This work aims to formulate educational transformation strategies to shift public perception toward more liquid and productive waqf practices. The analysis employs a descriptive qualitative methodology with a public policy study approach to evaluate the effectiveness of current regulations and curricula. Data were gathered through a review of statutory documents and literature concerning national waqf governance. The findings indicate that systemic policy intervention is required through the integration of modern philanthropy materials into madrasah and pesantren curricula, alongside strengthening the role of religious counselors as dissemination agents for contemporary fatwas. Policy criteria scoring reveals that updating teaching materials and digitalizing impact reporting are the most strategic steps to dismantle public cognitive barriers. The implementation of these recommendations is expected to significantly increase cash waqf penetration to strengthen the community's economic resilience. Through synchronization between educational authorities and Islamic financial institutions, the transition from traditional charity toward professional social investment can be achieved sustainably for the broader public benefit across Indonesia.